Direito do controle externo, direitos humanos e o direito constitucional internacional - Ramires, Rosana Laura de Castro Farias (2019)
In the scenario of a pluricent world society, highly connected by cognitive processes that revisit the traditional concept of soft law, the Supreme Audit Institutions appear involved in multilevel reticular relations with normative formations of constitutional, international and transnational orders, being assumed by global systems. UN and OECD human rights as indispensable entities for the promotion of rights related to the legal content of sustainable development law, and with them these systems expand their interactions. Through an inductive study of the relevant legislation and the practice of these different orders, aided by bibliographic and documentary research, this thesis addresses the concepts of external control law and the right to external control, in order to argue that these constitute the material sources of formation and scientific recognition of them and that transnationalization, oversight and external control activities, from a functional perspective, is a parallel movement to the internationalization of the right to external control, in favor of the effectiveness of human rights at all levels of systemic interaction. The study indicates that the functional and operational transnationalization of external oversight and control activities is a parallel movement to the internationalization of the right to external control as human rights, and that, on the one hand, this transnationalization increases the effectiveness of rights. Human rights through a human rights-based approach to external control law, on the other hand, has been compromised by the lack of legitimacy and compromise of the federative pact caused by the transnational performance, in particular, of the Brazilian Courts of Auditors. Although more research is needed to identify whether the transnationalization of external control constitutes a hypothesis of the institutionalization of a partial social system of world society, the study notes the effective intertwining arising from the conversation established between the transnational order of external control and the inter-national human rights order. as well as between those and the state legal order, indicating bottlenecks in international constitutional law and possible interpretative solutions. The state of knowledge reached, based on the analyzed works, can be used in other studies, with impact on the efficiency of the transnational order of external control and on the self-constitutionalization, or not, of this partial social order of world society